PENGENALAN AKTIFITAS CYBER THREAT HUNTING : STUDI KASUS HUNTING MALWARE DENGAN METODE MEMORY FORENSIC - Fadillah Nursyahiddin; Siti Zulfa Oktaviani; Lutvita Dwi Iklima; Feby Nurdiyanti (LPPM Universitas Widya Dharma, 2022)
Cyber Threat Hunting is one of the activities in the cyber security sphere that is currently developing. Threat Hunting shows the process of proactively searching for vulnerabilities and cybercrime actors through network media to anticipate cybersecurity incidents that will occur in a related infrastructure. Of course with this threat hunting, it will complement passive monitoring activities that only rely on alerts on SIEM (Security Information and Event Management), and the case study that I will raise is the threat hunting method at low level memory so that if there are cybercriminal actors who escape the system SIEM and possibly already on internal systems can be detected and can perform forensic and related system recovery activities